Systemic structural gender discrimination and inequality in the health workforce: theoretical lenses for gender analysis, multi-country evidence and implications for implementation and HRH policy - Constance Newman; Alice Nayebare; Ndeye Mingue Ndiate Ndiaye Gacko; Patrick Okello; Abdou Gueye; Sujata Bijou; Selly Ba; Sokhna Gaye; N'deye Coumba; Babacar Gueye; Yankouba Dial; Maimouna N'doye (BMC, 2023)
Abstract This commentary brings together theory, evidence and lessons from 15 years of gender and HRH analyses conducted in health systems in six WHO regions to address selected data-related aspects of WHO's 2016 Global HRH Strategy and 2022 Working for Health Action Plan. It considers useful theoretical lenses, multi-country evidence and implications for implementation and HRH policy. Systemic, structural gender discrimination and inequality encompass widespread but often masked or invisible patterns of gendered practices, interactions, relations and the social, economic or cultural background conditions that are entrenched in the processes and structures of health systems (such as health education and employment institutions) that can create or perpetuate disadvantage for some members of a marginalized group relative to other groups in society or organizations. Context-specific sex- and age-disaggregated and gender-descriptive data on HRH systems' dysfunctions are needed to enable HRH policy planners and managers to anticipate bottlenecks to health workforce entry, flows and exit or retention. Multi-method approaches using ethnographic techniques reveal rich contextual detail. Accountability requires that gender and HRH analyses measure SDGs 3, 4, 5 and 8 targets and indicators. To achieve gender equality in paid work, women also need to achieve equality in unpaid work, underscoring the importance of SDG target 5.4. HRH policies based on principles of substantive equality and nondiscrimination are effective in countering gender discrimination and inequality. HRH leaders and managers can make the use of gender and HRH evidence a priority in developing transformational policy that changes the actual conditions and terms of health workers' lives and work for the better. Knowledge translation and intersectoral coalition-building are also critical to effectiveness and accountability. These will contribute to social progress, equity and the realization of human rights, and expand the health care workforce. Global HRH strategy objectives and UHC and SDG goals will more likely be realized.